The Umbrella Review of VDR Gene Polymorphism and the Risk of Diabetes and Possible Implications in Immunotherapy - Kalmatovich, Kalmatov Romanbek; Omran, Karar Hassan; Kadhim, Yousif; Al-Marayaty, Shatha Sadiq; Kaleefa, Talib; Dinara, Makhanbetkulova (Trends in Immunotherapy, 2026)
Systematic reviews and meta-analyses investigated VDR gene polymorphism correlations with T1D and T2D outcomes. We reviewed and meta-analyzed all VDR gene polymorphism research, including clinical outcome case-control studies. We conducted a comprehensive review using systematic data analysis to evaluate the association between VDR gene polymorphism and the risk of diabetes. According to the predefined search strategy and selection criteria, the article reporting the correlations of FokI polymorphisms and the risk of T1D included 40 papers (5,406 cases and 7,507 controls). Forty-three papers (10,252 cases and 9466 controls) focused on the associations between the FokI polymorphisms and T2D risk. The articles evaluated 10,252 cases and 9466 controls. Six meta-analyses linked the Fokl gene polymorphism to T1D and T2D. Summaries were nominally significant in 50% of observational meta-analyses. We demonstrated no association between VDR gene polymorphism and T1D risk across different ethnicities. T2D risk was also highly connected to the FokI polymorphism in Asian ethnicity. Gene-environment interactions must be investigated to understand these associations. The FokI polymorphism in the VDR gene has been extensively investigated, but more research is needed to know how VDR SNPs cause DM. Diabetes risk is linked to VDR gene polymorphism in this study. Diabetes risk is linked to the VDR gene polymorphism in this study. More research and well-planned studies are necessary for certainty.